Characterization of the hydrogeological operation of the Comarsa-Peru open-pit mining unit applying geomatic technologies - Cabello, Cristian (2008)
The aim of this thesis is hydro-geological characterized a Santa Rosa Mining District (SMD). Digital Elevation Model (DEM), geological cartography, hydrogeological, mine data and different thematic maps, generated with Geographical Information Systems (GIS) and numerical models were used to characterize the hydrology of SMD. In several field campaigns were cartographies and inventoried 270 water point, four open pit and two types of metallurgical waste in an area of 878 Ha according to the results two aquifers wear delimited: Formation Chimú fractured aquifer and formation Inca Chulec karstic aquifer. Geological cartography and lineament maps show that the study area is cut by several faults and fractures in four main directions Open pit and fracture area controlled the aquifers recharge. Acid mine drainage (AMD) were observe in two open pit (Sacalla with pH=3.0 and Seductora with pH=3.8). According to main component obtained in 21 samples analysis in ground water in UMSR in possible observe three type of water: HCO3-Mg (2), HCO3B-Ca (2) and HCO3-Na (17).